Analysis of the Fitness Business in the VUCA World: A Case Study of Home Fitness Club - Wattana, Tanawat; Kangsadanporn, Korn (Journal of Dhamma for Life, 2025)
This research aims to 1) analyze the business environment of home fitness clubs, 2) present the direction of the business in the VUCA world, and 3) propose internal improvement guidelines for the business based on the 7s McKinsey Framework. This qualitative research was conducted through in-depth interviews with 11 key informants. The study found that 1) the VUCA world environment affecting home fitness clubs includes: (1) increased learning of skills and management from global sources, (2) marketing to expand a more diverse customer base, (3) lower rental costs for expanding branches, (4) difficulty in cost control, and (5) more complex management. The direction of home fitness clubs in the VUCA world includes: (1) focusing on quality and standard services, (2) providing attentive and friendly customer care, (3) offering professional services willingly, and (4) conducting business for social benefit. Internal improvement guidelines include: (1) focusing on cost control strategies, (2) adjusting the structure and management styles, (3) providing appropriate promotion and support for staff, (4) clear division of work and responsibilities, (5) regular personnel selection and knowledge development processes, (6) creating specialized skilled personnel, and (7) promoting shared values, emphasizing a passion for service and enjoyment in exercising, collective knowledge development, attentive and friendly service that makes customers feel at home, and helping customers achieve their personal goals. The study found that the improvement guidelines for home fitness businesses are: (1) continuously adjusting strategies according to the context and needs of customers, (2) developing the potential of personnel by focusing on quality service, (3) creating services that focus on the elderly to create business opportunities, (4) reducing prices by controlling costs, and (5) setting long-term goals through franchise expansion, and (6) conducting socially responsible business.